Gender issues in family business research: A bibliometric scoping review - Nguyen, Minh-Hoang (University of Economics Ho Chi Minh City, 2023)
Purpose The current review aims to examine the growth trajectory, most influential documents, intellectual and conceptual structure of the literature regarding gender issues in family business research. Design/methodology/approach The bibliometric analysis was performed using 224 documents from 1991 to 2020 extracted from the Web of Science database. Findings The review finds that this field's knowledge grew exponentially during the last three decades, mainly after 2003 and the last several years. Based on the co-citation analysis, three major research lines are identified: “Women's challenges and opportunities in the family business”, “Gender diversity in the family business corporate board”, and “Gender and family SMEs management.” The temporal co-word analysis reveals that “Gender diversity in the family business corporate board” is the latest research line. Originality/value By reviewing prominent cited references and documents that cited them, the authors provide the landscapes and research gaps of three major research lines for further development.